2020
DOI: 10.1111/eip.12937
|View full text |Cite
|
Sign up to set email alerts
|

The role of key workers in improving physical health in first episode psychosis: A scoping review

Abstract: Aim Studies have demonstrated that a majority of the decline in health status and functioning emerges during the first few years following the onset of psychosis. This knowledge led to the development of specialized early intervention services (EIS) targeting patients experiencing their first episode of psychosis (FEP). The central component of EIS is often assertive case management delivered by a multidisciplinary team, where an appointed key worker is responsible for coordinating treatment and delivering var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 77 publications
(113 reference statements)
1
7
0
Order By: Relevance
“…Our high‐retention rate meanwhile was like those reported in several similar studies (Firth et al, 2018; Korman et al, 2020; Teasdale et al, 2016; Usher et al, 2019; Williams et al, 2016). Meanwhile, our finding that participants valued keyworker support, particularly regarding physical health issues, reaffirms those of a recently published review of keyworker interventions for FEP patients (Lim et al, 2020). Also, we believe our findings are unique because they; (i) shed new light on the nature and potential of relationships between physical health keyworkers, FEP patients and third parties (particularly GPs) and (ii) demonstrate the acceptability of a telemedicine intervention for patients with severe mental health issues during the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our high‐retention rate meanwhile was like those reported in several similar studies (Firth et al, 2018; Korman et al, 2020; Teasdale et al, 2016; Usher et al, 2019; Williams et al, 2016). Meanwhile, our finding that participants valued keyworker support, particularly regarding physical health issues, reaffirms those of a recently published review of keyworker interventions for FEP patients (Lim et al, 2020). Also, we believe our findings are unique because they; (i) shed new light on the nature and potential of relationships between physical health keyworkers, FEP patients and third parties (particularly GPs) and (ii) demonstrate the acceptability of a telemedicine intervention for patients with severe mental health issues during the COVID‐19 pandemic.…”
Section: Discussionsupporting
confidence: 90%
“…The intervention was conducted from February through April 2020. As noted, it was informed by the MRC's Framework (Campbell et al, 2000), as well as our study protocol (McCombe et al, 2019), a scoping review conducted on keyworker involvement in FEP patient care (Lim et al, 2020), 10 semi‐structured interviews with healthcare professionals (general practitioners [GPs] and psychiatrists), steering group meetings, and Ireland's national model of care for FEP (Health Service Executive (HSE), 2019) and making every contact count initiatives (O'Brien & Scott, 2016). The intervention sought to provide keyworker led interventions that; (a) enhance FEP participants' physical health and (b) improve integration between healthcare providers (especially MHSs and GPs) regarding participants' physical health issues requiring follow‐up.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Lim et al. 's (2020) scoping review, referral to an Exercise Physiologists was suggested to promote better PH outcomes. However, our results identified that a reactive approach to provide more assertive care for concerning signs of PH deterioration was seen more widely in practice.…”
Section: Discussionmentioning
confidence: 99%